Investigating factors influencing firms marketing strategy creativity Effectiveness - Norazah Mohd Suki (2012)
This paper aims to examine factors influencing the relative importance of firms marketing strategy creativity. 100 completed and usable set of questionnaires was obtained from business managers, entrepreneurs and small business owner operating in surrounding Labuan areas in Malaysia. Data were analyzed by employing multiple regression analysis. Results revealed that Quality of Product and Technological Turbulence were found to be the leading factors influencing the relative importance of firms’ marketing strategy creativity. A creative strategy is the result of certain organizational characteristics and an appropriate strategy formulation process. The findings created an understanding of what attributes of external and internal factors influence the outcome of e-learning in high tech companies.